2018
DOI: 10.1002/cbdv.201700493
|View full text |Cite
|
Sign up to set email alerts
|

New Metabolites Produced by Cylindrocarpon sp. SY‐39 from a Driftwood

Abstract: Four novel compounds, cylindropyrone A (1), 10'-hydroxyilicicolinic acid D (3), cylindrolactones A (4) and B (5), together with known dihydroinfectopyrone (2) were isolated from the culture of Cylindrocarpon sp. SY-39 from a driftwood. Their structures were elucidated using 1D- and 2D-NMR spectroscopy. Compound 3 showed antimicrobial activity against Staphylococcus aureus with MIC value of 5.0 μg/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Compound 5 was isolated as a newly natural product, which was initially reported as a chemically synthesized product, named 4-chloro-5-methyl-2-((2E,6E)-3,7,11-trimethyldodeca-2,6,10-trien-1-yl)benzene-1,3-diol (5). The structure of 5 was determined by comparing NMR data [15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 5 was isolated as a newly natural product, which was initially reported as a chemically synthesized product, named 4-chloro-5-methyl-2-((2E,6E)-3,7,11-trimethyldodeca-2,6,10-trien-1-yl)benzene-1,3-diol (5). The structure of 5 was determined by comparing NMR data [15].…”
Section: Resultsmentioning
confidence: 99%
“…They have attracted extensive attention from pharmacologists. Owing to their distinctive structural diversity, they have been reported to exhibit a range of promising biological activities including antitumor [2], anti-inflammatory [3], antimicrobial [4,5], and anti-trypanosome [6,7]. Recent studies indicated that they showed potent hDHODH inhibitory activity, which means they have been involved in the treatment of cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports stated that Cylindroccarpon sp. are more likely to become plant pathogens, such as; root disease in almonds (Capote et al 2022); and stem diseases (Punja et al 2021); from roots of vines affected by black foot disease (Lawrence et al 2019); from rootstock of vines affected by black foot disease (Aigoun-Mouhous et al 2019); from plant disease Sapium ellipticum (Kamdem et al 2018); from driftwood disease (Suzuki et al 2018;Yoshida et al 2018); soilborne pathogens causing rot on ginseng roots (Han et al 2017); necrotic symptoms of strawberry roots (Adhikari et al 2013); shoot death symptoms on vines (Schroers et al 2008). In contrast to these reports, Cylindroccarpon sp.…”
Section: Discussionmentioning
confidence: 99%
“…6 ) was initially isolated from Cylindrocarpon sp. SY-39 in 2018 and displayed antimicrobial activity against S. aureus (MIC=5.0 µg/mL) 40 . Cylindrocarpol dimer ( 21 ) ( Fig.…”
Section: Overviewmentioning
confidence: 99%